2016
DOI: 10.1007/s12182-016-0125-2
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanisms and sequence response of authigenic grain-coating chlorite: evidence from the Upper Triassic Xujiahe Formation in the southern Sichuan Basin, China

Abstract: Authigenic grain-coating chlorite is widely distributed in the clastic rocks of many sedimentary basins around the world. These iron minerals were mainly derived from flocculent precipitates formed when rivers flow into the ocean, especially in deltaic environments with high hydrodynamic conditions. At the same time, sandstone sequences with grain-coating chlorites also tend to have relatively high glauconite and pyrite content. EPMA composition analysis shows that glauconites with ''high Al and low Fe'' conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Although extensive study has been conducted on the biomarkers of the continental source rocks in the Sichuan Basin (Lin, 2014; Shi et al., 2012; Yu et al., 2016), there are still some problems. Firstly, most studies are about the source rocks of the Late Triassic Formation, and only a few studies have been conducted on the Lower Jurassic source rocks.…”
Section: Introductionmentioning
confidence: 99%
“…Although extensive study has been conducted on the biomarkers of the continental source rocks in the Sichuan Basin (Lin, 2014; Shi et al., 2012; Yu et al., 2016), there are still some problems. Firstly, most studies are about the source rocks of the Late Triassic Formation, and only a few studies have been conducted on the Lower Jurassic source rocks.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the grain framework did not experience effective compaction, which can be inferred from the high cementation content (Figure 9(c)). The timing of authigenic grain-coating chlorite in sandstone is believed to be related to multiple sources (Bahlis and Luiz, 2013; Billault et al., 2003; Grigsby, 2001; Sun et al., 2014; Yu et al., 2016). Thin section and SEM analysis suggest grain-coating chlorite formed before feldspar dissolution and grains came into contact, because chlorite occurs between grain contacts (Figure 9(h)).…”
Section: Discussionmentioning
confidence: 99%
“…Small amounts of grain-coating chlorite have been found in the Xujiahe sandstone, showing a positive relationship with porosity and a slight relationship with permeability (Figure 14(e) and (f)). Previous studies have focused on the relationship of authigenic grain-coating chlorite with reservoir porosity preservation (Bloch et al., 2002; Ehrenberg, 1993; Huang et al., 2004; Xiang et al., 2016; Yu et al., 2016). They reported that grain-coating chlorite is beneficial to reservoir porosity preservation by enhancing resistance of compaction and inhibit growth of quartz cement, especially in deeply buried sandstone reservoirs (Bloch et al., 2002; Ehrenberg, 1993; Huang et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…2; Wang and Meng 2008;Zheng et al 2008;Zou et al 2013;Yu et al 2016;Ye et al 2017). During the depositional period of the Shaximiao Formation, the LMTB was relatively static, whereas the Micang-Daba Mountains Tectonic Zone (MDMTZ; Fig.…”
Section: Tectonic Evolution Of the Foreland Basinmentioning
confidence: 99%